Rini T, DESIGN OF ADDITIONAL TRAIN SCHEDULE INFORMATION SYSTEM IN PT. TRAIN INDONESIA (PERSERO) OPERATING AREA 2 BANDUNG - Rini Tisnawati (INFOKOM (Informatika & Komputer), 2018)
This research aims to determine the process of running systems as well as design and build additional train schedule information system at PT. Kereta Api Indonesia (Persero) Operation Area 2 Bandung. Based on the research results, the process of calculating the travel time of an additional train is still manually, so the calculation process to be slow and complicate in preparing reports and filing additional train schedule. Research methods used are surveys observations to research sites, interviews and literature review. The concept of this information system design is using object-oriented approach with UML modeling (Unified Modeling Language), and implemented with visual basic programming languages and MySQL as database. Software development method used is Waterfall. There were some suggestions which were needed for solving those problems : 1) using neural algorithms to make decision; 2) providing training for users of the application system; 3) developing system in the future.